Robust Real-Time Tracking for Visual Surveillance. (5th September 2006) - Thirde Thirde, David David; Borg Borg, Mark Mark; Aguilera Aguilera, Josep Josep; Wildenauer Wildenauer, Horst Horst; Ferryman Ferryman, James James; Kampel Kampel, Martin Martin
Abstract : This paper describes a real-time multi-camera surveillance system that can be applied to a range of application domains. This integrated system is designed to observe crowded scenes and has mechanisms to improve tracking of objects that are in close proximity. The four component modules described in this paper are (i) motion detection using a layered background model, (ii) object tracking based on local appearance, (iii) hierarchical object recognition, and (iv) fused multisensor object tracking using multiple features and geometric constraints. This integrated approach to complex scene tracking is validated against a number of representative real-world scenarios to show that robust, real-time analysis can be performed.